Lifelong learning: approaches to increasing the understanding of chemistry by everybody - Gilbert, John K. (2015)
This chapter is concerned with the need for increased efforts to both revise the school chemistry curriculum, so that more students are encouraged to persist in the study of the subject, and to make the ideas of chemistry more readily available and appealing to adults. The aim must be to provide increased opportunities for lifelong learning. Attention is focused on the educational principles that will guide such a provision. The potential of the various media, through which informal resources for learning about chemistry and the chemical technologies can be realistically provided, are evaluated. Finally, a summary of the actions suggested is provided.